The effect of distance learning and learning motivation on student learning satisfaction - Dinaria br Sembiring; Bena br Ginting; Pesta Gultom; Hermelina Ekasari br Tarigan (Enrichment : Journal of Management, 2022)
This research was conducted to find out how the Effect of Distance Learning and Learning Motivation on the learning satisfaction of semester V students majoring in computerized Accounting. AMIK Medicom. This study used three variables consisting of bound variables, namely student learning satisfaction (Y), while the free variables were distance learning (X1) and learning motivation (X2). The type of research used is explanatory research through associative research, which is research that aims to explain the influence between two or more variables. The population in this study was students in semester V of the computerized accounting department of AMIK Medicom totaling 51 people. The data collection method is carried out with a questionnaire of literature studies, and observation. Data analysis carried out in this study is a hypothesis test with a t-test (partial test) and an F-test (simultaneous test). The results of this study were obtained that: (1) based on the partial test of Distance Learning Affects the learning satisfaction of students in semester V majoring in computerized Accounting with a t-test of 4,147. (2) Based on the partial test, learning motivation affects the learning satisfaction of students of AMIK Medicom with a t-test of 3,285. (3) Based on the Simultaneous test of the Effect of Distance Learning and Learning Motivation on the Learning Satisfaction of AMIK Medicom Students with an F test of 7,814.